Comparison of divided versus loop sigmoid colostomy in the management of anorectal malformation - Naveed Haider; Imran Hashim; Asif Iqbal; Armaghan Ahmad; Soban Hameed; Arsalan Raza Wasti; Muhammad Saleem (Pediatric Surgery Research Center of Shahid Beheshti University of Medical Sciences, 2020)
Introduction: Anorectal malformation (ARM) is a birth defect of the digestive tract in which the anus and rectum are not normally developed. Surgical procedure such as colostomy (loop or divided) is suggested as the initial treatment for high variety ARM. Our objective was to compare frequency of stoma related complications of loop sigmoid colostomy versus divided sigmoid colostomy for high variety anorectal malformations. Materials and Methods: A randomized controlled trial was carried out at children's hospital and the institute of child health Lahore. A total of 180 patients were divided into two groups randomly using lottery method loop sigmoid colostomy (group-A) and divided sigmoid colostomy (group-B). After surgeries patients were followed weekly up till 4 weeks. Stoma related complications were noted. Results: The mean age in group A and group B were 3.22 ± 1.26 days and 3.36 ± 0.97 days respectively. In group A there were 77 male & 13 were female, in group B there were 67 male & 23 female patients. In group A 24.5% patients had complications: 3.4% patients had retraction, 11.1% had prolapse, 2.2% had Obstruction, parastomal hernia was seen in 5.6%, stoma necrosis were seen in 2.2%. In group B 20% patients had different complications: 2.2% patients had retraction, 2.2% had prolapse, 5.6% had obstruction, parastomal hernia were seen in 2.2% and stoma necrosis were seen in 7.8%. The complications in group A were higher when compared to group B but were not significant, p-value > 0.05. Conclusion: Divided sigmoid colostomy can be adopted to avoid stoma related complications in future.